Media primitivism : technological art in Africa - Collier, Delinda, 1973- (Visual arts of Africa and its diasporas., 2020)
"MEDIA PRIMITIVISM is a major work of media theory centering Africa. In order to redefine ideas of the medium and mediation, Delinda Collier deconstructs terms that have been formative in the conceptualization of African art (in particular, the fetish), rethinking them in light of another abstraction that shaped the media, art, and anthropological theory circulated in the twentieth century: Africa itself. Collier responds to the long preoccupation with Africa as the home of art that is "natural," non-technological, non-philosophical, exploring mediated African artworks that do not fit into these narratives. She argues that ideas about "African media" must be understood in relation to other modes of transfer and transmutation that have significant colonial and postcolonial histories, such as extractive mining and electricity. This new history demonstrates how pivotal artworks transcend the distinctions between the "made" and the "natural," thereby expanding ideas about mediation and about what African art can do. Each chapter considers the substances and concepts of a different technology-light, electricity, metals-to connect old and new media. Chapter 1, for example, provides an elemental reading of the canonical film work of Souleymane Cisse, arguing that his classic film Yeelen (1987) centers light and wind themselves as mediums. Chapter 2's discussion of one of the first pieces of electronic music, Halim El-Dabh's "Ta'abir Al-Zaar" (1944), shows how the role of electricity in African art cannot be understood only in relation to other new media forms that utilize electrified media. Punning on the multiple meanings of "medium" (zaar is a type of all-female spirit possession ceremony), El-Dabh's work brings together the technical and the spiritual. Chapter 4 turns to work by white South African artists to consider the relationship between (settler) colonial extraction and abstraction and the impossibility of standing outside of systems of oppression. Ultimately, Collier's book connects longstanding questions of art to the earliest moments of contact and cosmopolitan Africa"--